Su Jok therapy by twist and seed method of therapy to reduce the level of fear on COVID-19’s patient: a case series - Nurjannah, Intansari; Novianti, Zakiah; Suharto, Agus; Sudarmo, Muhammad Yasir; Hariyadi, Ki (International Journal of Research in Medical Sciences, 2021)
Patients with COVID-19 not only experience suffering from physiological symptoms but also psychological dimensions such as fear. Fear is part of life and the threat of self-existence will increase the fear level. Increased levels of fear will influence the process of healing by disturbing the immunity function. This case series reports the results of Su Jok therapy using the twist and seed method of therapy in reducing the level of fear of patients with COVID-19. Twenty cases of respondents with the average level of fear toward COVID-19 of ≥4 were included in this case reports. Fear level was measured by using the fear scale measurement (FSM). Su Jok therapy was conducted by twisting (120 times) and putting fenugreek seed on the joint of the patients’ index finger in Triorigin fixed joint correspondent of fear. Posttest of fear scale was measured after intervention in the intervals 5, 10 and 15 minutes. In all three interval measurements, there were significant improvements in the fear scale before and after Su Jok therapy (p=0.0001, p<0.05).